Home blood pressure control status in 2017‐2018 for hypertension specialist centers in Asia: Results of the Asia BP@Home study - Kario, Kazuomi; Tomitani, Naoko; Buranakitjaroen, Peera; Chia, Yook Chin; Park, Sungha; Chen, Chen Huan; Divinagracia, Romeo; Shin, Jinho; Siddique, Saulat; Sison, Jorge; Ann Soenarta, Arieska; Sogunuru, Guru Prasad; et al. (Wiley, 2018)
A self-measured home blood pressure (BP)-guided strategy is an effective practical approach to hypertension management. The Asia BP@Home study is the first designed to investigate current home BP control status in different Asian countries/regions using standardized home BP measurements taken with the same validated home BP monitoring device with data memory. We enrolled 1443 medicated hypertensive patients from 15 Asian specialist centers in 11 countries/regions between April 2017 and March 2018. BP was relatively well controlled in 68.2% of patients using a morning home systolic BP (SBP) cutoff of <135 mm Hg, and in 55.1% of patients using a clinic SBP cutoff of <140 mm Hg. When cutoff values were changed to the 2017 AHA/ACC threshold (SBP <130 mm Hg), 53.6% of patients were well controlled for morning home SBP. Using clinic 140 mm Hg and morning home 135 mm Hg SBP thresholds, the proportion of patients with well-controlled hypertension (46%) was higher than for uncontrolled sustained (22%), white-coat (23%), and masked uncontrolled (9%) hypertension, with significant country/regional differences. Home BP variability in Asian countries was high, and varied by country/region. In conclusion, the Asia BP@Home study demonstrated that home BP is relatively well controlled at hypertension specialist centers in Asia. However, almost half of patients remain uncontrolled for morning BP according to new guidelines, with significant country/regional differences. Strict home BP control should be beneficial in Asian populations. The findings of this study are important to facilitate development of health policies focused on reducing cardiovascular complications in Asia.